The Chemistry of HNO: Mechanisms and Reaction Kinetics - Michalski, Radosław; Smulik-Izydorczyk, Renata; Pięta, Jakub; Rola, Monika; Artelska, Angelika; Pierzchała, Karolina; Zielonka, Jacek; Kalyanaraman, Balaraman; Sikora, Adam Bartłomiej (Frontiers in Chemistry, 2022)
Azanone (HNO, also known as nitroxyl) is the protonated form of the product of one-electron reduction of nitric oxide (•NO), and an elusive electrophilic reactive nitrogen species of increasing pharmacological significance. Over the past twenty years, the interest in the biological chemistry of HNO has increased significantly due to the numerous beneficial pharmacological effects of its donors. Increased availability of various HNO donors was accompanied by great progress in the understanding of HNO chemistry and chemical biology. This review is focused on the chemistry of HNO, with emphasis on reaction kinetics and mechanisms in aqueous solutions.